A SYSTEMATIC LITERATURE REVIEW: ENGLISH SPECIFIC PURPOSE (ESP) FOR POLICE - Waluyo, Gatot Hadi; Lucky, Daniel; N, Nadila Mudea; Habibullah, Habibullah; Syafiq, Muhammad (Langue (Journal of Language and Education), 2024)
Abstract Nowadays, the use of systematic review is essential in reviewing many types of research, including English for specific purpose (ESP) research regarding police department. The evidence based of the systematic review integrates best research theoretical data based on expertise. This review systematically explains several journal articles which are contained about ESP for Police. Using two databases, namely Google Scholar and Scopus, 6 articles were extracted out of 62, from 2019 to 2023, with exclusion and inclusion criteria taken into consideration. Generally, this review is valuable for practitioners to know what journal articles are ready to be used in identifying gaps for research in ESP for Police.